ROTATING-DISK ELECTRODE VOLTAMMETRY - THE CATALYTIC MECHANISM (EC) AND ITS NUANCES - Compton, R; Day, M; Laing, M; Northing, R; Penman, J; Waller, A (1988)
The various mechanistic nuances of the catalytic (EC′) mechanism have been considered and it has been shown that steady-state rotating-disc voltammetry alone can discriminate between almost all of the various pathways considered. This deduction has been illustrated with reference to, first, the oxidation of the acetate anion in acetonitrile solution by means of the electrogenerated radical cation of tris(p-bromophenyl)amine and secondly, to the reduction of t-butyl bromide, in the same solvent, mediated through the radical anion of fluoranthene.